Archicraft: video game, architecture, Electronic entertainment research center - Wu, Tien-Wen Jack (My University, 2012)
Video games are no longer a means of simple entertainment that serve as a form of escapism. They are perceived not simply as free time distractions, but as logic of engagement and platforms of creative thinking. Furthermore, online video games have taken the idea of interaction to a level no any other media has ever achieved. Online video games known as virtual world or MMO (massively multiplayer online) are a mega interaction platform that attract millions of players across the globe. They are the ultimate goal that all architects have ever dreamed of, i.e. to create an interactive space that satis es the needs of users. This thesis research will tend to examine a variety of video games from 3 perspectives: space, structure and interactivity, with a view to understanding and exploring the behaviour of players in video games, as known as, virtual stages. In recognizing and articulating such behaviour, followed by exploring the relationship between architects, users and spaces, the interpretation of architectural languages can then be translated into physical spatial form. This research then questions the possibilities of promoting the gaming industry in South Africa. In the current digital era, the IT (information and technology) industry is a main stream profession that helps with the growth of a country as a whole. The role of the gaming industry therefore cannot be ignored in this instance. The gaming industry is a rapid growing profession that comprises a lot of speci c professionals. SA does not offer nor focus on the video game eld and as a result, we are experiencing a shortage of professionals in this eld. This thesis proposes a facility to facilitate current and future game industry related professionals, on the same time, providing a playful environment that integrates the building and local context, allowing deeper engagement for those who haven t been exposed to the real meaning behind video games.